Leveraging Company Revenue through Land and Building Fixed Asset Optimization Strategies in Commercial and Trading Companies - Jeane Asfita; Tatik Suryani; Linda Purnamasari (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
Leveraging business revenue through the utilization of fixed assets is crucial for companies. The purpose of this study is to examine and analyze the management of land and building fixed assets carried out by Commercial and Trading Companies. The research approach used is a descriptive qualitative approach with a case study method. The unit of analysis in this study is the Asset division of the Commercial and Trading company, namely PT Pertamina Patra Niaga Central Java Region (JBT). Data were collected through observation and interview methods, and triangulation was carried out using data collection methods, namely in-depth interviews with 5 informants who have different positions and duties, direct observation of the condition of the company's assets, and analysis of documents such as asset legal status documents, SOPs, and related operational records to validate the data. The results of the study found that asset optimization strategies to increase company revenue can be carried out by developing master policies and regional utilization guidelines supported by periodic evaluations, renovations and reassessments of idle assets to adjust market value to actual function, the application of digital technology to automate licensing and utilization monitoring, external collaboration in the form of leasing or collaboration with third parties. The implication of this study is that companies can provide strategic input to companies in an effort to improve the effectiveness and efficiency of fixed asset management